Distal Radioulnar Joint Osteoarthritis: An Update on Treatment Options - Katt, Brian M.; Tawfik, Amr; Zingas, Nicholas; Sirch, Francis; Beredjiklian, Pedro K.; Fletcher, Daniel (Journal of Hand and Microsurgery, 2021)
The distal radioulnar joint (DRUJ), the articulation between the sigmoid notch of the radius and the distal ulna, plays a pivotal role in stability and load bearing and allows for pronation and supination of the forearm. Osteoarthritis (OA) of the DRUJ commonly occurs due to distal radius trauma but may also be the result of conditions such as joint instability, septic arthritis, or primary OA. It is initially managed with conservative therapy, but surgery is often considered when nonoperative methods fail. The surgical approaches available to treat this pathology have grown over the years. The procedures have generally favorable outcomes, each with their own unique complications and considerations. This paper comprises a review of the outcomes and complications for the different procedures commonly used to surgically treat DRUJ OA.
Keywords: distal radioulnar joint; osteoarthritis; Darrach; Sauve-Kapandji; hemi-resection